Challenges of Curbing Criminality in Nigeria’s Maritime Domain and its Attendance Implications on Youth Empowerment - Etuk, Etiese (Advances in Social Sciences Research Journal, 2020)
Increasing cases of piracy, sea robbery, illegal bunkering and unauthorized mid-stream discharge, among several other criminalities, constitute a major source of concern to maritime administrations in the Gulf of Guinea, including that of Nigeria. Youth restiveness especially on the waterways of the Nigerian waters is of great concern to the government of Nigeria and the international communities. Youths grudges hinge on the gross negligence by the multinational oil exploration and production companies operating in the domains on areas of youth employment and empowerment, environmental devastation, education, negligence on environmental impacts restorations etc. While Nigerian current maritime security regulatory framework is not robust enough, enhancement must be made over time in order to continuously improve and deliver a secured maritime transportation system in Nigeria. The youths on the other hand inadvertently believe that by robbing in the water ways, kidnapping of individuals in the water ways for money, sabotaging oil pipelines, hijacking ships and vessels in the water ways and emptying their contents and then re-selling same to other buyers is a quick source of financial empowerment of the youths.